The Potential Role of Phytoplankton Functional Groups Under Anthropogenic Stressed Wetlands: Characterizing The Environmental Sensitivity. - Kumari, Suman; Gogoi, Pranab; Lianthuamluaia; Mishal, P.; Kumar Das, Basanta; Hassan, M. A.; Sarkar, U. K.; Das, A. K. (Environmental Management, 2024)
Anthropogenic and climatic changes are continuously altering the freshwater plankton, necessitating an evaluation of the complex structure of plankton communities to understand and mitigate these impacts. In this context, the present study focuses on evaluating the structure of plankton communities, specifically Phytoplankton Functional Groups (FGs) for assessing the environmental sensitivity of wetlands under changing scenario. These FGs are defined by shared adaptive features rather than taxonomic traits. Over the period from 2016 to 2018, two ecologically distinct wetlands were examined, analysing their phytoplankton FGs and their relationship with water quality parameters. Ecohydrological data revealed significant seasonal variations (p ≤ 0.05) in key parameters such as water depth, temperature, pH, electrical conductivity, dissolved oxygen, total alkalinity, total hardness, NO3-N, and PO4-P. Notably, there were no significant differences observed among the sampling stations within each wetland. A total of 125 phytoplankton genera/species were classified into 23 FGs in the open wetland and 22 FGs in the closed wetland. Spatial and seasonal analyses of dominant FGs suggested both wetlands were experiencing pollution pressures. This study highlights the powerful role of phytoplankton functional groups (FGs) as bioindicators of wetland health, uncovering pollution pressures. In open wetlands, 15 phytoplankton FGs with 36 key taxa (Indicator Value ≥ 40%) emerged as critical indicators, while in closed wetlands, only 10 FGs with 17 taxa were identified. To assess eutrophication, the occurrence of these indicator species was evaluated using BVSTEP function analysis. The study recommends pollution reduction in catchment areas and restoration of riverine connectivity to enhance FG diversity. Phytoplankton FG methodologies are deemed effective for assessing the environmental sensitivity of wetlands significantly impacted by human activities. This research offers a scientific foundation for the evaluation and restoration of wetland ecosystems. Highlights: Phytoplankton functional groups (FGs) serve as precise bioindicators of wetland environmental sensitivity and pollution pressures. Seasonal and spatial assessments of water quality reveal insights into wetland ecological health. The response of phytoplankton FGs to environmental factors effectively indicates water quality. Key plankton species were identified as indicators of wetland ecological sensitivity.